Evolution of solution-based organic thin-film transistor for healthcare monitoring- from device to circuit integration: a review - Yusof, Nur Syahadah; Mohamed, Mohamed Fauzi Packeer; Ghazali, Nor Azlin; Jalaludin Khan, Muhammad Firdaus Akbar; Shaari, Safizan; Mohtar, Mohd Nazim (Elsevier, 2022)
Demand for organic electronics has growth tremendously for the past decade, owing to their high flexibility and low processing cost attributes. As part of the important elements in organic electronics, a solution processable organic thin film transistor (OTFT) has been center of discussion among researchers. The OTFT is recognized to bring electrical, mechanical, and industrial benefits to a broad range of new applications such as flexible displays, radio frequency identification (RFID) tags, as well as biosensors specifically for healthcare monitoring system. Despite of their great application demand and significant technology advancement, the OTFT devices demonstrate unstable electrical performances especially in their mobilities and threshold voltages. These drawbacks will hold the fully commercialization of the OTFT in the market. Thus, this paper comprehensively reviews the current status of the OTFT technologies, ranging from material, device, process, and integration, including improvement that have been done on mobilities and operating voltages. Besides that, this work discusses on the applicability of the OTFT in the biosensor applications dedicated for real-time healthcare monitoring purposes. This review paper therefore is expected to provide a critical analysis on OTFT developments, as well as recognize their research gaps to allow their fully commercialization in the near future.